In Vitro Atheroprotective Effects of Trigonella Foenum Graecum (TFG) and its Saponins in LPS-Stimulated Human Coronary Artery Endothelial Cells - Radzi Ikhsan, Ahmad; Fromming, Gabriele Ruth Anisah; Muhamed T, Osman; Suhaila, Muid; Hapizah, Nawawi; Thuhairah Hasrah, Abdul Rahman (Walailak University, 2022)
There has been a shift towards utilizing natural products as an adjunct therapy to standard treatment in the prevention of coronary artery disease, and Trigonella foenum graecum (TFG) is one of the potential natural products of interest. In the present study, we attempted to determine the effects of TFG and its saponins on atherosclerosis related biomarkers in vitro. Protein expression of markers of inflammation, endothelial activation and transcription factors were measured by Procarta™ and ELISA assays. Gene expression of the same markers were determined by qPCR and the interaction between monocytes and HCAECs were evaluated through monocyte binding assay following 16 h of treatment with TFG and saponins. Both TFG and its saponins exhibited reducing effects on atherosclerosis-related markers. Based on the area under the curve (AUC) analysis, TFG reduced protein and gene expressions of ICAM-1 and VCAM-1 better than the saponins, while saponins reduced E-selectin expression better than TFG. Saponins showed a reduction of gene and protein expressions of IL-6, IL-8, NF-κB p50 and p65 better than TFG. TFG is more effective in reducing binding of monocytes to endothelial cells than saponins. TFG better reduced endothelial activation but exerted weaker anti-inflammatory effects than saponins, suggesting the possible synergism with other compounds in the crude extract which enhances attenuation of endothelial activation while inhibiting anti-inflammatory properties of saponins in the crude extract.